Analisa Pengaruh Jumlah Sudu dan Model Sudu Turbin Terhadap Daya Turbin Undershot Pembangkit Listrik Tenaga Mikro Hidro - Novia Utami Putri; Ernando Rizki Dalimunthe; Dwi Agus Riyanto; Resnandi Hendrawan Hendrawan (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2025)
Micro Hydro Power Plant is a small scale power plant that uses hydropower as its energy source. The power to drive the PLTMH turbine is in the form of water flow originating from irrigation canals and rivers. The undershot turbine is a type of water turbine that utilizes river flow or irrigation channels as the driving force for the undershot turbine. In this research, based on the problems used in undershot turbines in order to get maximum results, the researcher designed a PLTMH prototype by analyzing the effect of the number of blades and the turbine blade model on the power produced by the generator in the undershot turbine of a micro hydro power plant so that it would be known that the number of blades was 12 , 14, 18 and the triangular blade model which obtains better PLTMH output. In this study, the number of blades was 14 which was the best with a resulting voltage of 9.4 volts, a current of 0.96 amperes and a power of 9.02 watts.